The Role of Cancer-Associated Fibroblasts in Hepatocellular Carcinoma and the Value of Traditional Chinese Medicine Treatment - Jia, Wentao; Liang, Shufang; Cheng, Binbin; Ling, Changquan (Frontiers in Oncology, 2021)
Invasion and metastasis are the main reasons for the high mortality of liver cancer, which involve the interaction of tumor stromal cells and malignant cells. Cancer-associated fibroblasts (CAFs) are one of the major constituents of tumor stromal cells affecting tumor growth, invasion, and metastasis. The heterogeneous properties and sources of CAFs make both tumor-supporting and tumor-suppression effects possible. The mechanisms for CAFs in supporting hepatocellular carcinoma (HCC) progression can be categorized into upregulated aggressiveness and stemness, transformed metabolism toward glycolysis and glutamine reductive carboxylation, polarized tumor immunity toward immune escape of HCC cells, and increased angiogenesis. The tumor-suppressive effect of fibroblasts highlights the functional heterogenicity of CAF populations and provides new insights into tumor–stromal interplay mechanisms. In this review, we introduced several key inflammatory signaling pathways in the transformation of CAFs from normal stromal cells and the heterogeneous biofunctions of activated CAFs. In view of the pleiotropic regulation properties of traditional Chinese medicine (TCM) and heterogeneous effects of CAFs, we also introduced the application and values of TCM in the treatment of HCC through targeting CAFs.